Machine scheduling problems under deteriorating effects and deteriorating rate-modifying activities. Issue 3 (4th March 2018) - Zhang, Xingong; Wu, Wen-Hsiang; Lin, Win-Chin; Wu, Chin-Chia
Abstract: When the workers carry out the operation of many tasks, they will be fatigued. Meanwhile, the experience performance will also be degraded over time owe to mal-position or mal-alignment of jobs, abrasion of tools, etc. The maintenance activities will be required to maintenance acceptable production rates. In this study, some machine scheduling problems with deteriorating jobs and rate-modifying activities are investigated simultaneously. We assume the rate-modifying activity duration depends on the running time between the two rate-modifying activities. The objective functions are to minimize the makespan, the total completion time and the combination of the earliness, the tardiness, and the common due date. Polynomial-time algorithms are provided to optimally solve the three problems for the single-machine case. Finally, we also consider the parallelmachine problem to minimize only the total completion time by converting it into the corresponding assignment problem.